Pomen dosevkov in ozelenitev tal na vodovarstvenih območjih - Kramberger, Branko (University of Maribor Press, 2017)
The importance of Catch Crops and Soil Covernig in Water Protection Areas. After a period of strong intensification of agriculture production which was especially pronounced in the twentieth century at the turn of the third millennium, we are moving towards farming for environmental protection. Increased attention is being payed to the preservation of a clean atmosphere, biodiversity and clean groundwater. Based on a comprehensive overview of global scientific literature over the past twenty-five years and the results of our own research, the monograph presents the benefits of using catch crops for forage and catch crops in the exclusive function of soil covering during the periods of late autumn, winter, and early spring. The emphasis is on the importance for water protection areas. Special attention is paid to the negative effects that can occur through improper and incorrect use of catch crop soil covering and the risks of delayed mineralization of catch crop residue in the soil are analyzed in particular, as well as the effects on groundwater and on the proceeding crop in the field crop rotation. On the basis of a review of the specificity of individual groups of catch crops (Poaceae, Fabacea, Brassicaceae), the conclusion of the monograph provides technological recommendations for professionally justified use of catch crops for forage and soil covering in water protection areas.